Intravenous Lidocaine Is as Effective as Epidural Bupivacaine in Reducing Ileus Duration, Hospital Stay, and Pain After Open Colon Resection: A Randomized Clinical Trial. Issue 4 (1st June 2010) - Swenson, Brian R.; Gottschalk, Antje; Wells, Lynda T.; Rowlingson, John C.; Thompson, Peter W.; Barclay, Margaret; Sawyer, Robert G.; Friel, Charles M.; Foley, Eugene; Durieux, Marcel E.
Abstract : Background: Both postoperative epidural analgesia and intravenous (IV) infusion of local anesthetic have been shown to shorten ileus duration and hospital stay after colon surgery when compared with the use of systemic narcotics alone. However, they have not been compared directly with each other. Methods: Prospective, randomized clinical trial was conducted comparing the 2 treatments in open colon surgery patients. Before induction of general anesthesia, patients were randomized either to epidural analgesia (bupivacaine 0.125% and hydromorphone 6 μg/mL were started at 10 mL/hr within 1 hr of the end of surgery) or IV lidocaine (1 mg/min in patients <70 kg, 2 mg/min in patients ≥70 kg). Markers of return of bowel function, length of stay, postoperative pain scores, systemic analgesic requirements, and adverse events were recorded and compared between the 2 groups in an intent-to-treat analysis. Results: Study enrollment took place from April 2005 to July 2006. Twenty-two patients were randomized to IV lidocaine therapy and 20 patients to epidural therapy. No statistically significant differences were found between groups in time to return of bowel function or hospital length of stay. The median pain score difference was not statistically significant. No statistically significant differences were found in pain scores for any specific postoperative day or in analgesic consumption. Conclusions: No differences were observed between groups in terms of return of bowel function, duration of hospital stay, and postoperative pain control, suggesting that IV infusion of local anesthetic may be an effective alternative to epidural therapy in patients in whom epidural anesthesia is contraindicated or not desired.